Electrochemical promotion of propane oxidation on Pt deposited on a dense β″-Al2O3 ceramic Ag+ conductor - Tsampas, Michail; Kambolis, Anastasios; Obeid, Emil; Lizarraga, Leonardo; Sapountzi, Foteini; Vernoux, Philippe (Frontiers in Chemistry, 2013)
A new kind of electrochemical catalyst based on a Pt porous catalyst film deposited on a β"-Al2O3 ceramic Ag+ conductor was developed and evaluated during propane oxidation. It was observed that upon anodic polarization, the rate of propane combustion was significantly electropromoted up to 400%. Moreover, for the first time, exponential increase of the catalytic rate was evidenced during galvanostatic transient experiment in excellent agreement with EPOC equation.